An analysis of the practices of caesarean section in sub-Saharan Africa: A summary of the literature - Michel Dikete; Yves Coppieters; Philippe Trigaux; Yvon Englert; Philippe Simon; W Zhang (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Introduction: Ensuring access to quality caesarean sections (CS) is a challenge for the next millennium and a sustainable development goal to reduce maternal and infant mortality. A CS involves risks and complications and should therefore be performed in an approved way and not used excessively. The WHO recommends that the CS rate should not exceed 10-15%. Approximately 99% of maternal deaths occur in developing countries where efforts to reduce maternal deaths are still low. This review of the literature aims to provide a summary of CS practices in sub-Saharan Africa and the consequences in terms of morbidity and mortality.